2020
DOI: 10.1002/tax.12280
|View full text |Cite
|
Sign up to set email alerts
|

Circumscription and phylogenetic position of Ligularia sect. Stenostegia (Asteraceae: Senecioneae) based on morphological, cytological, and molecular phylogenetic evidence

Abstract: Ligularia sect. Stenostegia (Asteraceae: Senecioneae) has been questioned about its monophyly and phylogenetic position in our previous study. To settle the dispute, we here verify the phylogenetic pattern of L. sect. Stenostegia with a much denser taxon sampling in the section. The results have corroborated our previous hypothesis, by showing that L. sect. Stenostegia is monophyletic only after excluding L. lancifera, and that the core L. sect. Stenostegia is more closely related to Parasenecio and Sinacalia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It was once considered as an alpine variant ( Wulff 1944 ) or ecotype ( Drury 1967 ) of Ligularia . In addition, recent molecular phylogenetic studies focused on the LCP complex ( Ligularia - Cremanthodium - Parasenecio ; Asteraceae , Senecioneae ) ( Liu et al 2006 ; Ren 2012 ; Ren et al 2017 , 2020 ) revealed that the two genera are not monophyletic as traditionally defined. They together form three distinct and distantly related clades on chloroplast gene trees, with two clades having the species of the two genera interspersed between each other.…”
Section: Discussionmentioning
confidence: 99%
“…It was once considered as an alpine variant ( Wulff 1944 ) or ecotype ( Drury 1967 ) of Ligularia . In addition, recent molecular phylogenetic studies focused on the LCP complex ( Ligularia - Cremanthodium - Parasenecio ; Asteraceae , Senecioneae ) ( Liu et al 2006 ; Ren 2012 ; Ren et al 2017 , 2020 ) revealed that the two genera are not monophyletic as traditionally defined. They together form three distinct and distantly related clades on chloroplast gene trees, with two clades having the species of the two genera interspersed between each other.…”
Section: Discussionmentioning
confidence: 99%
“… Ligularia Cass. ( Asteraceae , Senecioneae ), with approximately 130 species recognized, is mainly distributed in eastern Asia ( Liu 1989 ; Liu et al 1994 ; Liu and Illarionova 2011 ; Ren et al 2020 ). The center of species diversity of the genus lies in the eastern Himalayas and the Hengduan Mountains region in southwestern China ( Liu et al 1994 , 2006 ; Liu and Illarionova 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Ericaceae ) was found in northern Mongolia by Oyunmaa and de Priest (2011) . Furthermore, representatives of some genera, which are listed in the flora of Mongolia ( Gubanov 1996 ; Urgamal et al 2014 ), have been revised in recent studies ( Podlech et al 2013 ; Sukhorukov et al 2013 , 2019 ; Wang et al 2014 ; Global Carex Group 2015 ; Duan et al 2016 ; Drew et al 2017 ; Kosachev 2017 ; Moore and Dillenberger 2017 ; Nosov et al 2017 ; Pimenov 2017 ; Wiegleb et al 2017 ; Boltenkov 2018 ; Gillespie et al 2018 ; Madhani et al 2018 ; Sinitsyna et al 2018 ; Zhang et al 2018 ; Barberá et al 2019 , 2020 ; Nobis et al 2019b ; Sramkó et al 2019 ; Akan et al 2020 ; Esput 2020 ; Friesen et al 2020 ; Murakami et al 2020 ; Nesom 2020 ; Ren et al 2020 ; Zaika et al 2020 ; Al-Shehbaz 2021 ; Al-Shehbaz et al 2021 ; Liu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%